The complete mitochondrial genome of the shoal chub, Macrhybopsis hyostoma. Issue 1 (1st January 2016) - Gaughan, Sarah; Johnson, Robin; Wang, Jun; Wachholtz, Michael; Steffensen, Kirk; King, Timothy; Lu, Guoqing
Abstract: The complete mitochondrial genome of the shoal chub ( Macrhybopsis hyostoma ) was determined to be 16, 899 bp and contained 22 tRNA genes, 2 rRNA genes and 1 control region. The whole genome base composition was 30.5% A, 28.5% T, 24.9% C and 16.1 G. This complete mitochondrial genome provides essential molecular markers for resolving phylogeny and future conservation efforts.